2020
DOI: 10.1186/s12885-020-06725-4
|View full text |Cite
|
Sign up to set email alerts
|

HOXB4 promotes the malignant progression of ovarian cancer via DHDDS

Abstract: Background: Homeobox B4 (HOXB4) is correlated with poor prognosis of various cancer types. However, how HOXB4 promotes ovarian cancer (OV) progression remains unclear. Methods: The Cancer Genome Atlas (TCGA) database indicated that a high level of HOXB4 in OV was correlated with poor prognosis. The biological functions of HOXB4 were confirmed by colony formation, migration, and invasion assays. The effect of HOXB4 on the expression of EMT cell markers was determined. The transcriptional target of HOXB4 was DHD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…HOXB4, a member of the Antp homeobox protein family, regulates embryonic development and participates in tumor progression as an oncogene or tumor suppressor gene. In ovarian cancer, the expression of HOXB4 was closely related to poor prognosis and transcriptionally activated DHDDS to stimulate the proliferation and invasion of tumor cells 23 . Other studies also revealed that HOXB4 was upregulated in ovarian cancer cells and drug-resistant cells 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOXB4, a member of the Antp homeobox protein family, regulates embryonic development and participates in tumor progression as an oncogene or tumor suppressor gene. In ovarian cancer, the expression of HOXB4 was closely related to poor prognosis and transcriptionally activated DHDDS to stimulate the proliferation and invasion of tumor cells 23 . Other studies also revealed that HOXB4 was upregulated in ovarian cancer cells and drug-resistant cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…HOXB4, the positive regulator implicated in the self-renewal of hematopoietic stem cells (HSCs) 21 , has been recognized as an oncogene or a tumor suppressor gene, depending on the specific type of cancer. HOXB4 was overexpressed in many cancers, including ovarian cancer 22 , 23 , cervical cancer 24 – 27 , lung cancer 28 , renal cancer 29 , mesothelioma 30 , and leukemia 31 34 , which promoted tumor growth and metastasis 23 . Moreover, increased HOXB4 expression resulted in drug resistance 31 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…CORO6 is a member of the coronin family and is an actin-binding protein [ 27 , 28 ]. HOXB4 is associated with the prognosis of ovarian cancer patients, leukemia resistance, and renal cancer [ 29 31 ]. RNF212 is associated with postoperative survival rate and TMZ chemoradiation response in GBM patients as well as mammalian meiosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HOXB4 participates in the advancement of ovarian cancer, as well as lung, prostate, and breast cancer ( 13 ). A previous report has shown that elevated HOXB4 expression facilitates the ovarian cancer progression via DHDDS ( 14 ). However, HOXB4 attenuates the tumorigenesis of cervical cancer cells by declining the Wnt/β-catenin signaling pathway activity ( 13 ).…”
Section: Introductionmentioning
confidence: 99%